Beneficial effects on vision in patients undergoing retinal gene therapy for choroideremia. (October 2018) - Xue, Kanmin; Jolly, Jasleen; Barnard, Alun; Rudenko, Anna; Salvetti, Anna; Patrício, Maria; Edwards, Thomas; Groppe, Markus; Orlans, Harry; Tolmachova, Tanya; Black, Graeme; Webster, Andrew; et al.
Abstract Retinal gene therapy is increasingly recognized as a novel molecular intervention that has huge potential in treating common causes of blindness, the majority of which have a genetic aetiology1–5 . Choroideremia is a chronic X-linked retinal degeneration that was first described in 18726 . It leads to progressive blindness due to deficiency of Rab-escort protein 1 (REP1). We designed an adeno-associated viral vector to express REP1 and assessed it in a gene therapy clinical trial by subretinal injection in 14 patients with choroideremia. The primary endpoint was vision change in treated eyes 2 years after surgery compared to unoperated fellow eyes. Despite complications in two patients, visual acuity improved in the 14 treated eyes over controls (median 4.5 letter gain, versus 1.5 letter loss, P  = 0.04), with 6 treated eyes gaining more than one line of vision (>5 letters). The results suggest that retinal gene therapy can sustain and improve visual acuity in a cohort of predominantly late-stage choroideremia patients in whom rapid visual acuity loss would ordinarily be predicted. The long-term follow-up results of a phase 1/2 retinal gene therapy clinical trial for choroideremia (NCT01461213 ) support the safety and efficacy of the treatment.